THE KUBED DIALECT SPEECH THROUGH TIME: PHONETIC FEATURES IN OLDER AND NEWER MATERIAL - Todorović, Suzana (Slavia Centralis, 2026)
This paper aims to examine the changing and preservation of selected phonetic features in the Kubed dialect speech, as documented by Tine Logar in Kubed in 1952. The diachronic analysis starts with a report, where the main Kubed phonetic characteristics are highlighted, and a fieldwork notebook with recorded dialectological data. These features are subsequently compared with those identified in the dialectological data from 1990, collected and recorded by a research team from Trieste (SDLA-SI I and II), and also with the specific features observed and recorded in Kubed in 2025. Given that the objective of the study was to illuminate the retention of Kubed’s phonetic traits among younger dialect speakers, participants between the ages of 35 and 55 were included.
Keywords: dialectology; dialect change; Slovenian Istrian dialect; Rižana subdialect; phonetics and phonology; diachronic study